Beach area development management (Case study: Pulo Swalan Beach, Pasarbanggi, Rembang Regency) - Al Muqsit, Faruq; Prihestiwi, Rosa Calista; Mussadun, Mussadun (Proceeding International Conference on Accounting and Finance, 2024)
Rembang Regency is known as the "City of Santri," with many Islamic boarding schools, and is the birthplace of great scholars throughout Indonesia. It is one of the regencies in Central Java Province that is included in the strategic area in terms of the economy for the RATUBANGNEGOR border corridor (Blora-Tuban-Rembang-Bojonegoro). This regency has a tourist area called Pantai Pulo Swalan, which has the potential for development, but the management of this existing area has yet to be maximized. Therefore, this article aims to develop beach area management so that it will be able to formulate area management procedures on Pulo Swalan Beach. The research method uses a quantitative approach, and data collection is secondary data with data collection techniques through literature studies and in-depth interviews. Data analysis comprises stakeholder mapping and a linear responsibility chart to determine management on Pulo Swalan Beach. From the result, it found that five stakeholders are involved in area management, but only two stakeholders have vital roles, namely the Rembang Regency government and the private sector, where the government’s role is more visible in making policies and supervising activities and the private sector plays a responsibility for the outcome. Therefore, a good stakeholder management concept is needed to ensure the optimal development of this area.